P2RY14 Is a Potential Biomarker of Tumor Microenvironment Immunomodulation and Favorable Prognosis in Patients With Head and Neck Cancer - Li, Qingxiang; Xu, Le; Li, Yuke; Yang, Rong; Qiao, Qiao; Wang, Yifei; Wang, Lin; Guo, Yuxing; Guo, Chuanbin (Frontiers in Genetics, 2021)
The tumor microenvironment (TME) has a crucial role in tumor development, progression, and treatment response. Yet, the exact interaction between cancer biology and the TME is not fully understood. The following study analyzes the correlation between immune/stromal/estimate scores and survival prognosis in head and neck squamous cell carcinoma (HNSC) using a bioinformatic method. As a result, a predictive biomarker, UDP-glucose-specific G(i) protein-coupled P2Y receptor (P2RY14), was discovered. The potential role of P2RY14-driven signaling pathways in the immune-remodeling of TME was then investigated. Briefly, low immune scores were associated with unfavorable prognosis and clinical-stage and tumor size, and the expression of P2RY14 was downregulated in HNSC patients. In addition, the survival analysis showed that HNSC patients with high expression had longer survival than patients with low expression from both TCGA databases and our own patients. We further discovered that P2RY14 is involved in the immune activity in the TME of HNSC; a downregulation of P2RY14 resulted in being an indicator for the conversion of TME status (from immune-dominant to metabolic-dominant status). The intersection analysis of genes co-expressed with P2RY14 indicated that the T-cell receptor signaling pathway and PD-L1 expression and PD-1 checkpoint pathway were candidates signaling pathways driven by the P2RY14 gene in HNSC. Further investigation of immune-associated signaling pathways regulated by P2RY14 may help HNSC patients gain higher immunotherapy benefits.